Menciptakan Peluang Bisnis Berdasarkan Kreativitas Mahasiswa Universitas Teknologi Sulawesi Utara - Diana Wangania; Christian Tarandung; Avent Patiro; Nathacia Rembet; Tonny Wangania; Only Tumiwa; Eva Lutia; Delvin Mamuko; Revally Nusa; Horvan Katulung (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This article describes the role of student creativity in creating innovative business opportunities. Through the exploration of creative ideas, students can be key drivers in identifying and developing untapped business opportunities. Understanding that creativity is the key to innovation, this article explains how students can apply their creative potential to create new and exciting business concepts. The focus lies on how creativity becomes a valuable resource to open doors to new opportunities, drive business growth, and make a positive contribution to the economy. By absorbing this approach, students are expected to see business opportunities as untapped fields of exploration, making creativity a catalyst for innovation in the world of entrepreneurship.